OS 01-07 CLINICAL IMPORTANCE OF COLLAGEN METABOLISM MARKERS IN RHEUMATIC HEART VALVE DISEASE IN INDIAN SUBPOPULATION. (September 2016) - Banerjee, Tanima; Mukherjee, Somaditya; Ghosh, Sudip; Biswas, Monodeep; Datta, Santanu; Pattari, Sanjib; Chatterjee, Shelly; Bandyopadhyay, Arun
Abstract : Objective: Rheumatic Heart Disease (RHD), a chronic acquired heart disorder results from Acute Rheumatic Fever. RHD is mostly prevalent in developing nations which is mainly diagnosed by transthoracic echocardiography. Till date, there is no biochemical marker for disease management. In the present study we aim to investigate whether mitral valve remodeling contributes to altered levels of circulating biomarkers of collagen metabolism in rheumatic heart disease. Design and Method: The study involved RHD subjects with before and after valve replacement surgery which includes age and sex matched controls. Subjects were evaluated by 2-dimensional transthoracic echocardiography. Subjects were classified into two groups- Mitral Stenosis (MS) and Mitral Regurgitation (MR). Carboxy-terminal propeptide of type I procollagen (PICP), amino-terminal propeptide of type III procollagen (PIIINP), total Matrix Metalloproteinase-1(MMP-1) and Tissue Inhibitor of Metalloproteinase-1 (TIMP-1) were assessed. Histopathological studies were performed in excised mitral valve sections.. A p value < 0.05 was considered statistically significant. Results: Plasma PICP and PIIINP concentrations increased significantly (p < 0.01) in MS and MR subjects compared to controls but decreased gradually over a one year period post mitral valve replacement (p < 0.05). In MS, PICP level and MMP-1/TIMP-1 ratio strongly correlated with mitral valve area (r = −0.40; r = 0.49 respectively) and pulmonary artery systolic pressure (r = 0.49; r = −0.49 respectively); while in MR they correlated with left ventricular internal diastolic (r = 0.68; r = −0.48 respectively) and systolic diameters (r = 0.65; r = −0.55 respectively). Receiver operating characteristic curve analysis established PICP as a better marker (AUC = 0.95; 95% CI = 0.91 – 0.99; p < 0.0001). Histopathology analysis revealed inflammation, neovascularisation and extensive leaflet fibrosis in diseased mitral valve. Conclusions: Monitoring plasma PICP may guide new strategies to disease management and can be clinically used to diagnose or monitor disease progression in Rheumatic heart disease.